EXPLORING L1 INTERFERENCE IN THE WRITINGS OF KADAZANDUSUN ESL STUDENTS - Pudin, Chelster Sherralyn Jeoffrey; Storey, John Mark; Len, Loh Yoke; Swanto, Suyansah; Din, Wardatul Akmam (Universitas Pendidikan Indonesia, 2015)
For many ethnic KadazanDusuns from Sabah, North Borneo, English is a third language after their mother tongue and Malay. The burden of having to contend with an additional language frequently leads to errors, particularly those caused by interference from the first language (L1). This study set out to identify the types and frequency of English language errors and their correlations in the writing of KadazanDusun ESL students at Universiti Malaysia Sabah. A further aim of the study was to establish which of these errors could be attributed to L1 interference. A total of 54 students with lower Malaysian University Entrance Test (MUET) band scores were asked to complete a questionnaire and write a short essay on a designated topic. The language errors were categorized and analysed via statistical analysis. Errors considered to be related to L1 interference were then identified after consultation with an experienced KadazanDusun language lecturer. The most common errors were those involving singular /plural nouns and unusual sentence structures. The results show that approximately 25% of the errors were attributable to L1 interference, i.e. mode (normal/involuntary), voice (actor (-ing form) /undergoer (-ed form), overuse of article, linker (when linker is used, no article is needed), auxiliary verb and direct translation. The findings of this study give ESL practitioners a better insight into student errors and should lead to improved writing performance in the classroom.